Self-Determination in the Life Dynamic Characteristics - Tsaruk, Inna (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2024)
The article examines the concept of self-determination as a mechanism for changing the life position of an individual, which is manifested in the dynamic characteristics of the way and style of life. There are two aspects of the way of life:  manner and image of life. The article establishes the essence of the difference between them. Since the way of a person’s life is represented simultaneously on two levels in the field of activity and on the cultural-historical plan, it is suggested to attribute human activity to the space of manner, while the cultural-historical plan should be taken to the space of image of life. On this basis, it is indicated that the manner of life is determined by the  activity of an individual, behavioral patterns and life strategies of activities that ensure the stability of the way of life, or may change it in situations of uncertainty, unexpected events, etc. It has been established that the image of life is the project space of a person's ideas about what his life should be like. In the space of the image of life,there exist ideals, standards, highest values, self-realization, freedom, integrity and other aspects to which a person always strives. It is in this space that the path to create a new life and discovering previously unknown opportunities for human self-development from the long-term perspectives. It was revealed that lifestyle is the space of communication and mutual relations of an individual with external and internal aspects of life that arise in a problematic situation. Lifestyle determines the establishment of a balance between the external set of social norms and rules of a new situation and the internally accepted expediency of their adoption and implementation. It is substantiated that self-determination is one of the leading mechanisms of self-change and individual development. In the context of a manner of life, self-determination ends with the transformation of an individual into a subject of action, which contributes to his adaptation to new circumstances. Self-determination in the space of lifestyle conditions the transformation of an individual into a subject of relations, which ensures his socialization and allows building relationships between the situation (others, life, the world, etc.) and himself on the basis of correctness in order to change them. It was revealed that in the space of the image of life, self-determination ensures the emergence of a subject-culture, creator of his own life story, integrated into the general cultural-historical content. Based on the obtained results, a scheme of practical support for persons in problematic situations was developed.